The Relationship Between Housing Density and Home Ventilation with the Incidence of Acute Respiratory Infection (ARI) Among Under-Five Children in the Coastal Area of Lingkar Timur Public Health Center, Bengkulu City - Rahmi Nurhayati; Yusran Fauzi; Wulandari Wulandari (Student Scientific Journal, 2026)
Background: Acute Respiratory Infection (ARI) remains one of the leading causes of morbidity and mortality among children under five, especially in coastal areas with high housing density and poor ventilation. Unhealthy home environments significantly increase the risk of ARI transmission. Objective: To determine the relationship between housing density and home ventilation with the incidence of ARI among children under five in the coastal area of the Lingkar Timur Public Health Center, Bengkulu City. Methods: This study employed an analytic observational design with a cross-sectional approach. The population consisted of 283 mothers with children under five, and 74 respondents were selected using a simple random sampling technique. Data were collected through interviews and home observations using questionnaires and observation sheets. Data analysis was performed using univariate and bivariate (Chi-square test, α = 0.05). Results: There was a significant relationship between housing density and ARI incidence (χ² = 13.455; p = 0.000) and between home ventilation and ARI incidence (χ² = 29.540; p = 0.000). Children living in houses with overcrowded and poorly ventilated conditions were at a higher risk of developing ARI. Conclusion: Housing density and ventilation are significantly associated with ARI incidence among children under five. Preventive efforts should include improving housing conditions, enhancing family health education, and strengthening community-based interventions to promote healthy homes.